APLIKASI PENGARUH PELAPISAN BENIH DENGAN PUPUK ORGANOMINERAL TERHADAP PERTUMBUHAN HASIL DAN EFISIENSI PEMBERIAN PUPUK UREA PADA TANAMAN JAGUNG DI VERTISOL LOMBOK TENGAH - Valentin, Baiq Heni; Priyono, Joko; Sutriono, Raden; Bhakti, Lalu Arifin Aria; Dewi, Rika Andriati Sukma (AGROTEKSOS, Jurnal Ilmiah Ilmu Pertanian, 2023)
The seed coating technique using organomineral fertilizer aims to reduce farming costs (fertilizer and fertilizing labor) so that farmer do not need to apply fertizers except for urea fertilizer which is not contained in organomineral fertilizers. This study aims to find out the effect of coating corn seeds with organomineral fertilizer on the growth of yields and efficiency of urea fertilizer delivery on corn crops in central Lombok vertisol in June to October 2021. The field experiment using the split plot experimental design with the main plot of seed coating treatment coated with organomineral fertilizer and as a child of plot with a dose of urea fertilizer consisting of three levels, namely 200, 300 and 400 kg urea / ha. The parameters studied are Dry Brangkasan Weight, Weight 100 Grains, Seed Yield, Pipilan Dry Weight, Plant Tissue Absorption N. The results showed that coating corn seeds with organomineral fertilizer had no real effect on all parameters. While the dose of urea fertilizer has no real effect on the Weight of Dry Brangkasan (BBK), Weight of 100 Grains, Seed Shortening and a real effect on The Dry Weight of Pipilan, Uptake of N Plant Tissue and Efficiency of Absorption N. The highest Yield of Dry Weight of Pipilan is obtained from Unsalted Seeds (BTB) on the provision of urea fertilizer 300 kg / ha. The efficiency of N uptake from Unsalted Seeds and Layered Seeds increased at urea fertilizer doses of 200 kg/ha ywhich is 77.62% and 75.71%.